Percentage Amplitude of Fluctuation Alterations in Multiple Frequency Bands in Patients With Transient Ischemic Attack: A Resting-State fMRI Study - Xinyun Li; Wei Zou; Fengjia Ni; Kelin He; Yingying Gao; Zhiyong Zhao; Yulin Song; Ruijie Ma (Neural Plasticity)
Conclusion: These findings suggest a significant impact of TIA on multiple brain regions, with frequency-specific alterations in PerAF, providing novel insights into the underlying mechanisms of TIA.